Assessing requirements for peacekeeping, humanitarian assistance, and disaster relief - Pirnie, Bruce, 1940-; Francisco, Corazon (Rand, 1998)
The purpose of this study is to assess requirements for peace operations, humanitarian assistance, and disaster relief, then to develop options for conducting such contingencies more effectively without detracting from the nation's capability to conduct major theater warfare. This study focuses on one aspect of requirements: those military units required to accomplish these types of operations. It reviews the history of operations during the period of interest, 1990-1996, assessing frequency, duration, and level of effort for each type of operation, expressed in military units. The authors then develop vignettes, or generalized patterns for each type of operation, to examine requirements--both peak strength and rotational demands--under broad projections of the level of future operations. Finally, they analyze implications for all armed services, but particularly for those Army units that are central to protracted land operations and those Air Force units that are required to secure no-fly zones and conduct strikes. The report concludes by recommending options that would improve capability. These options are mostly changes or adjustments at the margin, because U.S. forces have clearly demonstrated that they have sufficient capability to perform these operations successfully. The authors especially recommend organization of Army contingency brigades and air expeditionary forces optimized for close air support. Together, these would be a powerful, versatile force appropriate for a wide range of contingencies. The prospective audience includes decisionmakers and supporting staffs within the Office of the Secretary of Defense and the Joint Staff, and also the services for areas falling within their cognizance.